Annual Plan 1993-94 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1993)
Heads of Development - Outlay and Expenditure Physical Targets and Achievements Minimum Needs Programme - Physical Targets and Achievements Statement Regarding Externally / Aided Projects Outlays by Head of Development - For District Plans Centrally Sponsored Schemes.
Government of Pondicherry, Planning and Research Department